National audit of perinatal HIV infections in the UK, 2006–2013: what lessons can be learnt?. Issue 4 (16th January 2018) - Peters, H; Thorne, C; Tookey, PA; Byrne, L
Abstract : Objectives: The aim of the study was to investigate circumstances surrounding perinatal transmissions of HIV (PHIVs) in the UK. Methods: The National Study of HIV in Pregnancy and Childhood conducts comprehensive surveillance of all pregnancies in women diagnosed with HIV infection and their infants in the UK; reports of all HIV‐diagnosed children are also sought, regardless of country of birth. Children with PHIV born in 2006–2013 and reported by 2014 were included in an audit, with additional data collection via telephone interviews with clinicians involved in each case. Contributing factors for each transmission were identified, and cases described according to main likely contributing factor, by maternal diagnosis timing. Results: A total of 108 PHIVs were identified. Of the 41 (38%) infants whose mothers were diagnosed before delivery, it is probable that most were infected in utero, around 20% intrapartum and 20% through breastfeeding. Timing of transmission was unknown for most children of undiagnosed mothers. For infants born to diagnosed women, the most common contributing factors for transmission were difficulties with engagement and/or antiretroviral therapy (ART) adherence in pregnancy (14 of 41) and late antenatal booking (nine of 41); for the 67 children with undiagnosed mothers, these were decline of HIV testing (28 of 67) and seroconversion (23 of 67). Adverse social circumstances around the time of pregnancy were reported for 53% of women, including uncertain immigration status, housing problems and intimate partner violence. Eight children died, all born to undiagnosed mothers. Conclusions: Priority areas requiring improvement include reducing incident infections, improving ART adherence and facilitating better engagement in care, with attention to addressing the health inequalities and adverse social situations faced by these women.